Examining the Impacts of Virtual Reality (VR) on Self-Directed Learning in EFL: A Mixed-Methods Study - Tanashur, Panji; Oktavia, Sonia; Aprianto, Dedi (Journal of Languages and Language Teaching, 2025)
The study examines how VR enhances self-directed learning in EFL by overcoming traditional methods’ limitations, boosting autonomy and engagement. While previous studies highlighted VR's positive effects on student engagement in language learning, its impact on SDL remains underexplored, with limited quantitative evidence and scarce qualitative insights into subjective experiences. This study used a mixed-methods approach, combining quantitative analysis to identify measurable trends and qualitative insights for a deeper understanding of VR’s influence on SDL. A survey of 194 EFL students used VR and SDL questionnaires, analyzed through simple linear regression. To enrich findings, semi-structured interviews with 13 participants explored their experiences. The findings showed that there is a positive effect of VR use on SDL, as indicated by the regression coefficient of 0.945, meaning that a 1% increase in the level of VR use is related to a 0.945 increase in self-directed learning p<0.05. The ANOVA results confirmed the reliability of the regression model in explaining the relationship between VR and SDL, with a significance of 0.000. R-squared value of 0.927, indicating that 92.7% of SDL variability is explained by VR. This demonstrates VR’s strong enhancement of SDL in EFL students, improving their autonomy and engagement in language learning. Adjusted R-squared value of 0.926 further confirms VR’s significant impact on SDL. Qualitative findings identified three key benefits of VR: higher engagement and motivation, improved access and flexibility, and cognitive reflection through self-reflection. The findings highlight VR's effectiveness as an active learning strategy that promotes independent learning by enhancing learner autonomy and engagement. In EFL contexts, VR-based strategies support interactive, self-paced learning, contributing to increased motivation and language retention.